2020
DOI: 10.11621/pir.2020.0308
|View full text |Cite
|
Sign up to set email alerts
|

The Construct Validity of the Russian Version of the Modified Academic Self-Regulation Questionnaire (SRQ-A) among Elementary and Middle School Children

Abstract: Background. The Academic Self-Regulation Questionnaire (SRQ-A) is a useful self-report measure of academic motivation grounded in self-determination theory (E. Deci & R. Ryan). Objective. The aim of the present study was to evaluate the utility of the Russian version of the SRQ-A by reporting psychometric properties, examining the factorial structure of the SRQ-A, and assessing its construct validity in a large sample of primary and middle school children. Design. To validate the Russian version of the SRQ-A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
4
0
4
Order By: Relevance
“…The items are loaded under the relevant factors in line with the original version and each factor contains five items. This finding is consistent with the results of research on self-regulation questionnaires based on SDT (Ryan & Connell, 1989;Black & Deci, 2000;Williams, et all, 1996;Levesque, et all, 2007;Gordeeva, Sychev, Lynch, 2020). In addition, the findings showed that CR, convergent and divergent validity are also desirable and the four dimensions of friendship self-regulation, while related to each other, are separate factors.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The items are loaded under the relevant factors in line with the original version and each factor contains five items. This finding is consistent with the results of research on self-regulation questionnaires based on SDT (Ryan & Connell, 1989;Black & Deci, 2000;Williams, et all, 1996;Levesque, et all, 2007;Gordeeva, Sychev, Lynch, 2020). In addition, the findings showed that CR, convergent and divergent validity are also desirable and the four dimensions of friendship self-regulation, while related to each other, are separate factors.…”
Section: Discussionsupporting
confidence: 89%
“…The results of research on gender differences showed that there is a difference between the two genders only in interjected regulation and RAI and women has a higher average. Soenens & Vansteenkiste (2005) also in their study reported significant gender differences in favor of women in SRQ-A and SRQ-F. Gordeeva, Sychev, Lynch (2020) also reported gender differences in self-regulation. In their study, women had a higher average in all dimensions except external regulation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Para validar las propiedades psicométricas de la escala, se realizaron varios análisis examinando la estructura factorial de cada subescala del SRQ-A. Los resultados apoyaron la validez de este instrumento, siguiendo la línea de otros estudios similares con diferentes traducciones de la escala original en estas edades mencionadas (Gomes et al, 2019;Gordeeva et al, 2020;Kröner et al, 2017).…”
Section: Discusión Y Conclusionesunclassified